JAPANESE IRIS (IRIS ENSATA THUNB.) IN SOUTHERN WEST SIBERIA - Z. V. Dolganova (Вавиловский журнал генетики и селекции)
Japanese varieties of Iris ensata Thunb. were being imported to Russia for more than 100 years ago by several scientists (E. Regel, N.I. Vavilov, V.M. Nosilov, V.T. Palvelyev), and in 1980s these varieties were tested in the Central Botanical Garden of RAS and in most cases, they failed (Rodionenko, 2002; Mironova, 2008). The first varieties were developed by G.I. Rodionenko. Japanese varieties were successfully introduced under forest-steppe conditions of the Altai Territory at the Lisavenko RI of Horticulture for Siberia (RIHS), and then breeding was conducted with the participation of retro varieties developed in 1980–1982. Crossing of geographically distant varieties, first, French and Japanese, and then, Altai, Far-Eastern, Leningrad and American, brought about 150 adapted ornamental genotypes and 15 of I. ensata varieties. In the progeny of varieties with simple flowers, genotypes with double and half-double flowers were selected, and in the progeny of the last ones, fertile genotype with 12 lobes of perianth. Pollen quality of the selected I. ensata genotypes was nearly as good as in the Altai species I. ruthenica and I. glaucescens: pollen fertility was 77,6 %, and viability, 53,1 %. Fruit formation of cultivars with simple flowers was 54 %, with double, 9 %, and with forced crossing 93 and 73 %, respectively. The fruit contained 5–116 seeds; their weight was 6–9 g; and germinative capacity, 1–37 %. Seedlings of 3–20 % plants of a group came to flowering in 3–5 years. Eight donors with high productivity, new colour, and flower shape were selected. During breeding, flower diameter increased from 12 to 20 cm; the width of upper perianth lobes, from 2 to 8 cm; and lower, from 7 to 9 cm. The range of flower colouring extended to 11 groups.